2002
DOI: 10.1034/j.1601-0825.8.s2.7.x
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and inhibition of HIV‐1 infection: molecular mechanisms

Abstract: Oral fluids are rarely a vehicle for HIV-1 infection in vivo, unlike other mucosal secretions. This unique property raises questions regarding (1) the molecular mechanisms responsible for the lack of salivary transmission, (2) the extent to which oral immunological responses mirror responses at other mucosal sites, (3) the use of promising salivary markers of HIV-1 disease progression, (4) the relationship between oral and blood viral loads, (5) cofactors that influence oro-genital transmission, and (6) the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…The panel of neutralizing antibodies used in this study represents both the previous generation of monoclonal antibodies (mAbs) with potent neutralization of subtype B HIV-1, yet importantly also includes more recently identified mAbs with extensive breadth even against the previously ''difficult to neutralize'' HIV-1 subtype C. The resistance profiles found for the infant clones described here are similar to other studies of newly infected infant viral variants of several HIV-1 subtypes. 14,16,36,41 While we saw little neutralization to 1b12 (Table 1) compared to some other studies where 50% or more of viruses were sensitive, 41,42 the results were similar to our previous study of uncultured Envelope pseudotypes from virus newly transmitted from mother to child. 15 Only one study of three infants infected through breast milk 39 also analyzed sensitivity to the recently identified broadly neutralizing PG9 and PG16 antibodies.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The panel of neutralizing antibodies used in this study represents both the previous generation of monoclonal antibodies (mAbs) with potent neutralization of subtype B HIV-1, yet importantly also includes more recently identified mAbs with extensive breadth even against the previously ''difficult to neutralize'' HIV-1 subtype C. The resistance profiles found for the infant clones described here are similar to other studies of newly infected infant viral variants of several HIV-1 subtypes. 14,16,36,41 While we saw little neutralization to 1b12 (Table 1) compared to some other studies where 50% or more of viruses were sensitive, 41,42 the results were similar to our previous study of uncultured Envelope pseudotypes from virus newly transmitted from mother to child. 15 Only one study of three infants infected through breast milk 39 also analyzed sensitivity to the recently identified broadly neutralizing PG9 and PG16 antibodies.…”
supporting
confidence: 75%
“…These antibodies clearly have enhanced breadth that includes neutralization of subtype C, and for this reason may represent a useful tool for passive immunization in regions where clade C HIV-1 is prevalent. 41 These data in particular support the CD4 binding site as a promising target for infant vaccine design.…”
mentioning
confidence: 83%
“…Endogenous anti-HIV-1 activity has been demonstrated in whole, parotid, and submandibular/sublingual (sm/sl) saliva, colostrum, whole milk, and seminal plasma (1,11,13,24,29,32,38,45,46,51) but not in cerebrospinal fluid or urine (38). The incidence of oral HIV-1 transmission is very low and can be attributed both to endogenous salivary factors that prevent oral excretion of transmissible levels of virus (45,47,48) and to lysis of HIV-infected cells due to the hypotonicity of saliva (2,3).…”
mentioning
confidence: 99%
“…It has been well described for the past decade or more that a variety of salivary inhibitors decrease HIV-1 infectivity in the oral cavity (108,109). Nonetheless, ongoing studies have suggested that oral transmission of the virus remains quite common in a number of important settings in vivo (6,7,51).…”
mentioning
confidence: 99%